2006
DOI: 10.1073/pnas.0601486103
|View full text |Cite
|
Sign up to set email alerts
|

Spatial remapping of touch: Confusion of perceived stimulus order across hand and foot

Abstract: The ''body schema,'' a spatial representation of the body in its environment, has been suggested to be an emergent property of a widespread network of effector-specific frontal and parietal areas, many of which integrate sensory input from the different modalities. On a behavioral level, such multimodality has been shown with temporal order judgment tasks, in which participants decide which of the two hands received a tactile stimulus first. The accuracy of these judgments is influenced by body posture, indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
113
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(126 citation statements)
references
References 56 publications
(88 reference statements)
10
113
3
Order By: Relevance
“…Intriguingly, this contrasts with previous research that has shown that the addition of non-spatial information, such as when the stimuli differ in the identity of the stimulated body part, has little if any effect on the deficit (Schicke & Roder, 2006;Shore et al, 2002). For instance, TOJ crossing effects are comparable when same or different fingers of each hand are stimulated (Shore et al, 2002), or even when stimuli are applied to one hand and to one foot, while they are crossed with each other (Schicke & Roder, 2006). Moreover, the effect of crossing the arms when stimuli differs in frequency or duration is comparable to any standard crossing effect (see Figures 2 and 6 in Roberts & Humphreys, 2008; though see Badde, Röder, et al, 2015, where TOJ crossing effects are reduced when location, but also non-spatial characteristics of the stimuli, are reported in a dual task).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, this contrasts with previous research that has shown that the addition of non-spatial information, such as when the stimuli differ in the identity of the stimulated body part, has little if any effect on the deficit (Schicke & Roder, 2006;Shore et al, 2002). For instance, TOJ crossing effects are comparable when same or different fingers of each hand are stimulated (Shore et al, 2002), or even when stimuli are applied to one hand and to one foot, while they are crossed with each other (Schicke & Roder, 2006). Moreover, the effect of crossing the arms when stimuli differs in frequency or duration is comparable to any standard crossing effect (see Figures 2 and 6 in Roberts & Humphreys, 2008; though see Badde, Röder, et al, 2015, where TOJ crossing effects are reduced when location, but also non-spatial characteristics of the stimuli, are reported in a dual task).…”
Section: Discussioncontrasting
confidence: 99%
“…Intriguingly, this contrasts with previous research that has shown that the addition of non-spatial information, such as when the stimuli differ in the identity of the stimulated body part, has little if any effect on the deficit (Schicke & Roder, 2006;Shore et al, 2002). For instance, TOJ crossing effects are comparable when same or different fingers of each hand are stimulated (Shore et al, 2002), or even when stimuli are applied to one hand and to one foot, while they are crossed with each other (Schicke & Roder, 2006).…”
Section: Discussioncontrasting
confidence: 86%
“…In one study, van Elk et al (2013) showed that the foot PPS (as measured by a visuotactile crossmodal congruency task) is mostly unaffected by factors such as limb posture and the congruency of a fake limb placed nearby, whereas the hand PPS is sensitive to these factors. In addition, other studies suggest that the lower limbs are slower (when compared to the hands) at remapping tactile information (e.g., Schicke and Röder 2006). So it might not be surprising that the lower limb PPS size differs from the upper limb PPS size.…”
Section: Discussionmentioning
confidence: 99%
“…Further, some neurophysiological evidence in monkeys suggests that the dorsal areas of the ventral premotor cortex (Muakkassa and Strick 1979;Kurata et al 1985;Kurata 1989) and medial regions of area 7 (Hyvärinen 1981) might be responsible for a 'foot-centered' PPS network, though an investigation using dynamic sensory stimuli was never formally reported. Thus, behavioural studies have uncovered the presence of PPS around the legs and feet (Schicke and Röder 2006;Schicke et al 2009;Van Elk et al 2013;Pozeg et al 2015;Scandola et al 2016;Stettler and Thomas 2016), but no study, to the best of our knowledge, has specifically examined how far PPS extends for the lower body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation